Cryoneurolysis to treat the pain and symptoms of knee osteoarthritis: a multicenter, randomized, double-blind, sham-controlled trial. Issue 8 (August 2017) - Radnovich, R.; Scott, D.; Patel, A.T.; Olson, R.; Dasa, V.; Segal, N.; Lane, N.E.; Shrock, K.; Naranjo, J.; Darr, K.; Surowitz, R.; Choo, J.; et al.
Summary: Objective: Evaluate the efficacy and safety/tolerability of cryoneurolysis for reduction of pain and symptoms associated with knee osteoarthritis (OA). Design: Randomized, double-blind, sham-controlled, multicenter trial with a 6-month follow-up in patients with mild-to-moderate knee OA. Patients were randomized 2:1 to cryoneurolysis targeting the infrapatellar branch of the saphenous nerve (IPBSN) or sham treatment. The primary endpoint was the change from baseline to Day 30 in the Western Ontario and McMaster Osteoarthritis Index (WOMAC) pain score adjusted by the baseline score and site. Secondary endpoints, including visual analogue scale (VAS) pain score and total WOMAC score, were tested in a pre-defined order. Results: The intent-to-treat (ITT) population consisted of 180 patients ( n  = 121 active treatment, n  = 59 sham treatment). Compared to the sham group, patients who received active treatment had a statistically significant greater change from baseline in the WOMAC pain subscale score at Day 30 ( P  = 0.0004), Day 60 ( P  = 0.0176), and Day 90 ( P  = 0.0061). Patients deemed WOMAC pain responders at Day 120 continued to experience a statistically significant treatment effect at Day 150. Most expected side effects were mild in severity and resolved within 30 days. The incidence of device- or procedure-related adverse events was similar in the two treatment groups with no occurrence of serious or unanticipated adverse device effects (ADE). Conclusions: Cryoneurolysis of the IPBSN resulted in statistically significant decreased knee pain and improved symptoms compared to sham treatment for up to 150 days, and appeared safe and well tolerated.